Systematic Strategy for the Development of Glycosyltransferase Inhibitors: Diversity-Oriented Synthesis of FUT8 Inhibitors - Manabe, Yoshiyuki; Hizume, Koki; Takakura, Yohei; Takamatsu, Shinji; Miyoshi, Eiji; Kamada, Yoshihiro; Hurtado-Guerrero, Ramón; Fukase, Koichi (Synlett, 2024)
Glycans control various biological processes, depending on their structures. Particularly, core fucose, formed by α1,6-fucosyltransferase (FUT8), has a substantial influence on multiple biological processes. In this study, we investigated the development of FUT8 inhibitors with structural elements encompassing both the glycosyl donor (GDP-fucose) and acceptor (N-glycan) of FUT8. To efficiently optimize the structure of FUT8 inhibitors, we employed a strategy involving fragmentation of the target structure, followed by a structure optimization using a diversity-oriented synthesis approach. This study proposes an efficient strategy to accelerate the structural optimization of middle molecules.
Keywords: compound libraries; diversity-oriented synthesis; glycosyltransferase; enzyme inhibitor; diversity-oriented synthesis